ANALISIS EFEKTIVITAS DAN EFISIENSI PENYIMPANAN ARSIP (STUDI KASUS DI KANTOR CAMAT TIUMANG) KABUPATEN DHARMASRAYA SUMATERA BARAT - Eka Susi Susanti; Armida Silvia (Jurnal Ecogen, 2018)
The aims of  this research is to reveal how effective and efficience archival storage at Tiumang su-district office. The type of research is descriptive and qualitative research. The sampling technique used is the technique Snowball Sampling. Data collection techniques used were observation, interviews and documentation. The research instrument used is the interview guide and a tape recorder. Data analysis technique used is the model of Miles and Huberman. To test the validity of the data used triangulation technique. These results indicate that the archive storage at Tiumang su-district office not yet effective and eficience . This is evident from the files stored  not use archival storage system , the amount of equipment and supplies were inadequate and the lack of skilled personnel in the field of archives . Keywords :effectiveness and efficience Storage of  Archive